2019
DOI: 10.1111/jphp.13100
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro and in situ assessment of the efflux of five antidepressants by breast cancer resistance protein

Abstract: Objectives Antidepressants need to penetrate the blood-brain barrier (BBB) to exert their functions in the central nervous system. Breast cancer resistance protein (BCRP), an efflux transporter abundantly expressed in the BBB, prevents the accumulation of many drugs in the brain. This study aimed to identify whether five commonly used antidepressants (sertraline, duloxetine, fluoxetine, amitriptyline and mirtazapine) are BCRP substrates. Methods A combination of bidirectional transport and intracellular accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Breast cancer resistant protein (BCRP) is an ABC transporter expressed in different tissues, including the brain epithelial cells, and may be responsible for the low bioavailability of several psychotropics. A recent study showed that sertraline is a BCRP substrate along with its P-gp inhibiting properties ( Feng et al, 2019 ). Venlafaxine dose-dependently induces the BCRP expression ( Bachmeier et al, 2011 ).…”
Section: Breast Cancer Resistant Proteinmentioning
confidence: 99%
“…Breast cancer resistant protein (BCRP) is an ABC transporter expressed in different tissues, including the brain epithelial cells, and may be responsible for the low bioavailability of several psychotropics. A recent study showed that sertraline is a BCRP substrate along with its P-gp inhibiting properties ( Feng et al, 2019 ). Venlafaxine dose-dependently induces the BCRP expression ( Bachmeier et al, 2011 ).…”
Section: Breast Cancer Resistant Proteinmentioning
confidence: 99%
“…Ko143 and MK-571 have been widely used as the chemical inhibitor of BCRP and MRP4 in vitro and in vivo (Bertollotto et al, 2018;Drennen et al, 2018;Kanda et al, 2018;Feng et al, 2019). Hence, we have selected and used Ko143 and MK-571 to inhibit the transport activities of BCRP and MRPs in our study.…”
Section: Discussionmentioning
confidence: 99%
“…From another point of view, it is important to bear in mind that several antidepressant drugs are known as substrates of efflux transmembrane ATP-binding cassette (ABC) proteins, including P-glycoprotein (P-gp; ABCB1; MDR1) [55][56][57][58][59] and Breast Cancer Resistant Protein (BCRP; ABCG2) [60]. These transporters are expressed in several tissues, namely the intestine, kidney, liver, and blood-brain barrier (BBB).…”
Section: Pharmacokinetics Of Antidepressantsmentioning
confidence: 99%
“…The aforementioned results regarding P-gp and BCRP in the intestine suggest that their substrates may have higher bioavailability if administered in the morning, when the expression levels of efflux transporters are lower. Although sertraline is a known BCRP substrate [60], there are no studies in literature concerning the influence of the circadian BCRP oscillations on its intestinal absorption.…”
Section: Pharmacokinetics Of Antidepressantsmentioning
confidence: 99%